Application of MPS and FEM based Fluid-Structure Interaction Model to a Sequential Dam-Break Problem on Çoruh River - Abdullah Demir; Ali Ersin Dinçer (Doğal Afetler ve Çevre Dergisi)
Studies about fluid-structure interaction (FSI) problems do not have a long history. Fluid and structure has been separately modelled with different formulations by researchers. However, studies about FSI are limited and problems investigated in these studies are mostly out of civil engineering areas. Problems such as dam-breaking, flood effect on structure, slushing effect and tsunami are the problems consisting of a fluid structure interaction in civil engineering. The present study, a fluid structure interaction model is developed by using moving particle semi-implicit method (MPS) and finite element method (FEM) for fluid and structure, respectively. The developed code is applied to an idealized sequential dam-break problem. The effect of failed upper dam on the lower dam body is investigated in terms of pressure readings. Besides, behavior of flood in lower reservoir is observed with given profiles of surface water. Both results can be used for future studies and taking protective measures.